2022
DOI: 10.1111/tpj.16021
|View full text |Cite
|
Sign up to set email alerts
|

Pan‐genome and multi‐parental framework for high‐resolution trait dissection in melon (Cucumis melo)

Abstract: SUMMARY Linking genotype with phenotype is a fundamental goal in biology and requires robust data for both. Recent advances in plant‐genome sequencing have expedited comparisons among multiple‐related individuals. The abundance of structural genomic within‐species variation that has been discovered indicates that a single reference genome cannot represent the complete sequence diversity of a species, leading to the expansion of the pan‐genome concept. For high‐resolution forward genetics, this unprecedented ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…Due to the high degree of fragmentation of the Illumina-based published assembly, we could not conclude after contig alignment. As Chang-Bougi belongs to the makuwa botanical group, we mapped the two contigs to the publicly available genomes from this group: Early Silver Line, Ohgon and Sakata’s Sweet (Oren et al, 2022). We identified a very large and size-conserved insertion (ranging from 862 to 871 kb) at the breakpoint between the two contigs obtained for Chang-Bougi (Figure 8A).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high degree of fragmentation of the Illumina-based published assembly, we could not conclude after contig alignment. As Chang-Bougi belongs to the makuwa botanical group, we mapped the two contigs to the publicly available genomes from this group: Early Silver Line, Ohgon and Sakata’s Sweet (Oren et al, 2022). We identified a very large and size-conserved insertion (ranging from 862 to 871 kb) at the breakpoint between the two contigs obtained for Chang-Bougi (Figure 8A).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, melon (Cucumis melo) was the most frequently studied species within this plant family in terms of genome sequencing. Over the years, ten papers [67,[70][71][72][73][74][75][76][77][78] have described the sequences of different melon subspecies, varieties and cultivars. The first genome sequence of C. melo was revealed in 2012, as the second species after the cucumber genome in the Cucurbitaceae family.…”
Section: Cucurbits Genomes Complexity and Characterisationmentioning
confidence: 99%
“…An important work contributing greatly to the discovery of melon genomes was published in 2022 by the team of Oren et al [73]. The authors sequenced the genomes of 25 different melons, i.e., they provided 17 accessions of "melo" subspecies (in detail: 5x inodorus, 4x cantalupensis, 2x reticulatus, 2x khandalak, 1x duda'im, 1x flexuosus, 1x ameri and 1x adzhur cultivars), 7 for "agrestis" subspecies (2x chinensis, 1x conomon, 3x makuwa and 1x momordica), and 1 for C. collosus var.…”
Section: Cucurbits Genomes Complexity and Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Melons ( Cucumis melo L., Cucurbitaceae) are cultivated in almost all tropical regions of the planet, thus generating a wide diversity of phenotypic characteristics, especially size, shape, skin color and texture, pulp color, sugar content, acidity, flavor, and aroma. Melon is among the most consumed fruits in the world, among those with a large amount of pulp [ 1 ]. Some studies have demonstrated consumer preference for orange-fleshed melons [ [2] , [3] , [4] ].…”
Section: Introductionmentioning
confidence: 99%